2011
DOI: 10.3109/07420528.2011.574766
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Daily Rhythms of Wrist Temperature Between Obese and Normal-Weight Women: Associations With Metabolic Syndrome Features

Abstract: The circadian rhythm of core body temperature is associated with widespread physiological effects. However, studies with other more practical temperature measures, such as wrist (WT) and proximal temperatures, are still scarce. The aim of this study was to investigate whether obesity is associated with differences in mean WT values or in its daily rhythmicity patterns. Daily patterns of cortisol, melatonin, and different metabolic syndrome (MetS) features were also analyzed in an attempt to clarify the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 55 publications
11
74
1
Order By: Relevance
“…The results of this study showed that these lean women, after 1 week of eating late, suffered from metabolic alterations that usually characterise obese women, such as decreased glucose tolerance, decreased resting energy expenditure and decreased carbohydrate oxidation. Moreover, late eaters had a flattened pattern of daily cortisol and alterations in daily rhythms of body temperature similar to those that characterise obese women as previously described (39) . In Table 3, we summarise the specific recommendations for the prevention of obesity and MetS by improving the circadian system health, based on available scientific evidence proved in epidemiological, clinical and experimental animals (A); on interventional studies in human subjects or in animal models (B); and on preliminary studies or low number of studies (C).…”
Section: What Can We Do? We Can Change What How and When We Eatsupporting
confidence: 78%
“…The results of this study showed that these lean women, after 1 week of eating late, suffered from metabolic alterations that usually characterise obese women, such as decreased glucose tolerance, decreased resting energy expenditure and decreased carbohydrate oxidation. Moreover, late eaters had a flattened pattern of daily cortisol and alterations in daily rhythms of body temperature similar to those that characterise obese women as previously described (39) . In Table 3, we summarise the specific recommendations for the prevention of obesity and MetS by improving the circadian system health, based on available scientific evidence proved in epidemiological, clinical and experimental animals (A); on interventional studies in human subjects or in animal models (B); and on preliminary studies or low number of studies (C).…”
Section: What Can We Do? We Can Change What How and When We Eatsupporting
confidence: 78%
“…29 Moreover, our group has previously demonstrated that the increase in the rhythm fragmentation with obesity is related to a decrease in melatonin amplitude, which has been described as a biological sign of chronodisruption. 26 It is important to highlight the fact that in the current work, significant differences were found in IV between high responders and low responders, whereas no significant differences were found in the IS, which suggests that these differences in wristtemperature variables were not because of phase instability.…”
Section: Discussionmentioning
confidence: 55%
“…25 Interestingly, among the differences in circadian parameters, the reduced amplitude found in low responders is one of the hallmarks of aging. An attenuated amplitude has been observed in elderly subjects as well as in the obese 26 and in Alzheimer's patients. 24,27 A healthy wrist-temperature pattern that characterizes ideal body-weight individuals shows wide amplitude with high-temperature values during sleep time and a pronounced drop after arising in the morning with low values during wake time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The lifestyle of any person is a well-defined rhythmic phenomenon and it is controlled by the circadian system (Corbalán-Tutau et al, 2011). This system coordinates living organisms with their changing environments and allows them to perform those biochemical, physiological, or behavioral functions that ensure the survival of all species at the proper times.…”
Section: Introductionmentioning
confidence: 99%